Creating and Enhancing Capacity in Africa for Efficient Economic and Social Development - Cole, Lawalley (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
We estimate that by 2050, one-third of the world’s population will live in Africa: up from about one-fifth in 2012. Such growth will be imbalanced across Africa with Southern and North African countries characterised by slowing or even negative youth population growth, while West Central, and East African countries will experience significant youth population increases. Sub-Saharan Africa will have a considerably higher youth–to-population ratio over the next 35 years. The continent must, therefore, be ready for an increasingly young labour force.